Evidence for SARS-CoV-2 Spike Protein in the Urine of COVID-19 Patients. Issue 6 (24th June 2021) - George, Santosh; Pal, Anasuya Chattopadhyay; Gagnon, Jacqueline; Timalsina, Sushma; Singh, Pallavi; Vydyam, Pratap; Munshi, Muhammad; Chiu, Joy E.; Renard, Isaline; Harden, Christina A.; Ott, Isabel M.; Watkins, Anne E.; et al.
Visual Abstract: Abstract: Key Points: Using an antigen capture assay to detect severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike S1 protein, we found that the protein is present in the urine of 25% of patients with coronavirus disease 2019 (COVID-19). Further, we found that 24% and 21% of adult patients with COVID-19 have high levels of urine albumin and cystatin C, respectively. The presence of SARS-CoV-2 spike protein in the urine suggests renal abnormalities resulting from COVID-19. Background: SARS-CoV-2 infection has, as of April 2021, affected >133 million people worldwide, causing >2.5 million deaths. Because the large majority of individuals infected with SARS-CoV-2 are asymptomatic, major concerns have been raised about possible long-term consequences of the infection. Methods: Wedeveloped an antigen capture assay to detect SARS-CoV-2 spike protein in urine samples from patients with COVID-19whose diagnosis was confirmed by positive PCR results from nasopharyngeal swabs (NP-PCR+) forSARS-CoV-2. We used a collection of 233 urine samples from 132 participants from Yale New Haven Hospital and the Children's Hospital of Philadelphia that were obtained during the pandemic (106 NP-PCR+ and 26 NP-PCR−), and a collection of 20 urine samples from 20 individuals collected before the pandemic. Results: Our analysis identified 23 out of 91 (25%) NP-PCR+ adult participants with SARS-CoV-2 spike S1 protein in urine (Ur-S+). Interestingly, although all NP-PCR+ children were Ur-S−, one child who was NP-PCR− was found to be positive for spike protein in their urine. Of the 23 adults who were Ur-S+, only one individual showed detectable viral RNA in urine. Our analysis further showed that 24% and 21% of adults who were NP-PCR+ had high levels of albumin and cystatin C, respectively, in their urine. Among individuals with albuminuria (>0.3 mg/mg of creatinine), statistical correlation could be found between albumin and spike protein in urine. Conclusions: Together, our data showed that one of four individuals infected with SARS-CoV-2 develop renal abnormalities, such as albuminuria. Awareness about the long-term effect of these findings is warranted.